2016
DOI: 10.26226/morressier.5770e29ed462b80290b4c7a4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing Levonorgestrel-releasing intrauterine system (Mirena) and medroxyprogesterone acetate as a therapy for endometrial hyperplasia

Abstract: Background: This study was designed to evaluate the comparison of insertion of levonorgestrel (LNG)-releasing intrauterine system versus oral medroxyprogesterone acetate on endometrial hyperplasia in a randomized controlled trial. Materials and Methods: A total of 60 women with the initial histopathological diagnosis of endometrial hyperplasia in two groups received LNG or medroxyprogesterone (10 mg/d orally) for 12 days a month for 3 months). Endometrial biopsy was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…The strengths of this study are that the design was prospective, and patients were selected consecutively, which minimised bias. In addition, 68% of AH/Stage Ia EEC patients responded to the LNG-IUS by 12 months, with AH showing a higher response rate compared to Stage I EEC, similar to previous studies [7][8][9][10][11] supporting that the sample is representative of the background patient population. Baseline serum HE4 was also positively associated with patient age, BMI, menopause, in agreement with previous studies [17,18,[22][23][24]30,31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The strengths of this study are that the design was prospective, and patients were selected consecutively, which minimised bias. In addition, 68% of AH/Stage Ia EEC patients responded to the LNG-IUS by 12 months, with AH showing a higher response rate compared to Stage I EEC, similar to previous studies [7][8][9][10][11] supporting that the sample is representative of the background patient population. Baseline serum HE4 was also positively associated with patient age, BMI, menopause, in agreement with previous studies [17,18,[22][23][24]30,31].…”
Section: Discussionsupporting
confidence: 87%
“…Studies have shown that oral progestogens can reverse AH and Stage Ia EEC in 70-75% patients by 12 months [2][3][4][5][6]. Further studies have shown that the levonorgestrel-releasing intrauterine system (LNG-IUS) produces fewer systemic side effects and regression rates of 84-100% in AH [7][8][9][10][11] and 68% in stage I EEC [12]. This has led to increased use of the LNG-IUS compared to oral progestogens as a conservative therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A RCT of 60 participants in total, compared EH treatment with the 52 mg-IUD/10–20 mcg-LNG-14t to MPA 10 mg orally daily for 12 days monthly for 3-months [ 20 ]. The 52 mg-IUD/10–20 mcg-LNG-14t achieved an 89.3% regression rate without any cases of disease progression, whereas cyclic MPA had a 70.4% regression rate with 7.4% disease progression [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…A RCT of 60 participants in total, compared EH treatment with the 52 mg-IUD/10–20 mcg-LNG-14t to MPA 10 mg orally daily for 12 days monthly for 3-months [ 20 ]. The 52 mg-IUD/10–20 mcg-LNG-14t achieved an 89.3% regression rate without any cases of disease progression, whereas cyclic MPA had a 70.4% regression rate with 7.4% disease progression [ 20 ]. While hirsutism occurred significantly more often in the MPA group, p = 0.013, this study, which did not use intent to treat analysis, was underpowered for the 18.9 percentage-point regression rate difference to achieve statistically significance [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation